ANALYSIS OF RECOGNITION OF INCOME AND EXPENSES AT UPT PUSKESMAS BILOKKA KEC. PANCA LAUTANG - Rahmawati Rahmawati; Amrizal Salida; Ari Ayu (Universitas Ichsan Sidenreng Rappang, 2024)
The phenomenon that occurs in this research is that in recognizing income, the payment portion using BPJS still uses the cash basis method in recognizing it, while the PSAP regulations require agencies to use the accrual basis method in preparing financial reports. The aim and objective of this research is to analyze the recognition of income and expenses at UPT. Bilokka District Health Center. Panca Lautang. The benefits of this research are that it is hoped that it will provide benefits for the author, for UPT. Bilokka District Health Center. Panca Lautang, and for Institutions. The type of research used in this research is qualitative research using a narrative approach. This research was conducted at JL. Poros Soppeng, Bilokka sub-district, Panca Lautang sub-district. The data used are primary and secondary data. The techniques used in collecting data are observation, interviews and documentation techniques. The data analysis used is data reduction, data presentation, and drawing conclusions. The data validity tests used are source triangulation, technical triangulation, and time triangulation. From the results of the research carried out in this thesis, it was found that the method used by UPT. Bilokka Community Health Center is not right. This is because the method used to recognize income still uses cash basis recognition, unlike expense recognition which is recognized using accrual basis recognition.